Fluxes over Varanasi during intensive observation period of MONTBLEX-90 (MAUSAM, 1995)
ABSTRACT. MONTBLEX-90 data for an Intensive Observational Period (IOP) was extracted to investigate the thunderstorm and its impacts on surface layer at Varanasi on 27 July 1990. Sensible heat flux has been computed by profile, aerodynamic and eddy correlation methods. In addition to that. momentum and moisture fluxes have been computed for comparative diagnosis of situations before, at the time and after thunderstorm, Monin-Obukhov similarity theory has been used for quantification of the fluxes. Findings indicate that surface is more buoyant at the time of thunderstorm. Under this influence, maxima of moisture and momentum fluxes occur at the tin1e of thunderstorm. However, heat flux was found to be maximum before the thunderstorm, The results provide an understanding of surface layer turbulent transfer during stable and unstable conditions.